2017
DOI: 10.1186/s12943-017-0605-z
|View full text |Cite
|
Sign up to set email alerts
|

HOXC8 regulates self-renewal, differentiation and transformation of breast cancer stem cells

Abstract: BackgroundHomeobox genes are master regulators of cell fate during embryonic development and their expression is altered in cancer. By regulating the balance between cell proliferation and differentiation, they maintain homeostasis of normal tissues. Here, we screened the expression of homeobox genes in mammary stem cells to establish their role in stem cells transformation in breast cancer.MethodsUsing a Homeobox Genes PCR array, we screened 83 homeobox genes in normal cancer breast stem/progenitor cells isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 69 publications
(95 reference statements)
1
35
0
Order By: Relevance
“…Finally, they showed that the induction of HOXA5 expression was correlated with ATRA-mediated apoptosis and cellular growth inhibition [255,256]. More recently, similar down-regulated expression was found for HOXC8 gene in breast CSCs, and associated with DNA methylation in its gene promoter and expression of miR196 family members (Figure 3) [257].…”
Section: Homeobox (Hoxs) Genes Impaired Expressionmentioning
confidence: 62%
“…Finally, they showed that the induction of HOXA5 expression was correlated with ATRA-mediated apoptosis and cellular growth inhibition [255,256]. More recently, similar down-regulated expression was found for HOXC8 gene in breast CSCs, and associated with DNA methylation in its gene promoter and expression of miR196 family members (Figure 3) [257].…”
Section: Homeobox (Hoxs) Genes Impaired Expressionmentioning
confidence: 62%
“…Among these miR-NAs, miR-582 has been reported to promote tumorigenesis by targeting phosphatase and tensin homolog in colorectal cancer [36]. Moreover, miR-196b promotes cell migration and invasion by targeting FOXP2 in hepatocellular carcinoma and regulates self-renewal, differentiation, and transformation by targeting HOXC8 in breast cancer stem cells [37,38]. miR-9 has an inhibitory role in papillary thyroid cancer by targeting BRAF and reduces metastatic behavior in triple-negative breast cancer by targeting NOTCH1 [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in basal like breast cancer cells, Chaffer and colleagues observed that ZEB1 promoter of non-CSCs is maintained in a bivalent configuration and in response to TGFβ, the chromatin switches to an active state leading to the transcription of ZEB1, consequently converting non-CSCs to CSCs (Chaffer et al, 2013). On the other hand, loss of function of HOXC8, a homeobox gene, in non-tumorigenic mammary epithelial cells due to its promoter DNA hypermethylation has been shown to be associated with CSC pool expansion, increased self-renewal and a transformed phenotype (Shah et al, 2017). A histone modifier, enhancer of zeste homolog 2 (EZH2) is a core member of polycomb repressor complex 2 (PRC2) and mediates transcriptional repression of target genes via the trimethylation of lysine 27 of histone 3 (H3K27me3) (Gan et al, 2018).…”
Section: Mechanisms Controlling Csc Plasticitymentioning
confidence: 99%